Pengaruh Kepercayaan Diri Terhadap Kemampuan Berpikir Kreatif Matematis Siswa Melalui Model Problem Based Learning Berbantuan Google Classroom - Mimbarwati Mimbarwati; Mulyono Mulyono; Tri Suminar (Departement of Mathematics Education, 2023)
The purpose of this study was to analyze the effect of self-confidence on students' mathematical creative thinking skills through GCR-assisted PBL learning. This research method is quantitative research. The research design used in quantitative research is quasi-experimental (quasi-experimental), namely a research design that involves two groups (experimental and control). This quasi-experimental study used a nonequivalent control group design. The subjects of this study were fourth grade students at SD Negeri in Gugus Ki Hajar Dewantara Pati. The planned research implementation time will be carried out in the second semester of the 2022/2023 school year. The data collection technique is using a description test, while the analysis technique in this study is using a simple linear regression test. In this disclosure, it shows that the results of students' self-confidence have an effect on students' mathematical creative thinking abilities quantitatively which are very good by looking at the value of the coefficient of determination R-Square = 0.160 (16%) meaning that the ability to think creatively mathematics affects self-confidence by 16%. The coefficient value of the creative thinking test results is 0.156 which shows an increase of 15.6% and the coefficient value is positive meaning that between students' self-confidence and students' mathematical creative thinking abilities have a positive relationship and influence each other towards a balanced and balanced increase.